1962
DOI: 10.1017/s0031182000024215
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of esterase enzymes in Ascaris lumbricoides

Abstract: 1. The distribution of non-specific esterase and of cholinesterase in Ascaris lumbricoides has been determined using histochemical methods.2. Non-specific esterase has been shown to be present in the cuticle, in the walls of the excretory canals, in the innervation processes of the muscles, in the coelomocytes, in the oesophageal glands, in the intestine, in the rectal glands, in the male and female reproductive systems, in parts of the nervous system and as 'caps' of enzyme on fat globules in the hypodermis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1963
1963
2006
2006

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(23 citation statements)
references
References 29 publications
(31 reference statements)
1
22
0
Order By: Relevance
“…The authors did not find any trypsin activity in any sample. In the present study, no lipase activity was found in any part of the A. suum organism, but esterase or esterase lipase were found in all samples, which is consistent with the results obtained by Lee (1962a), who found esterase activity in all the parts of the A. suum organism. Żółtowska and Łopieńska (1999) found the activity of lipase in all examined parts of A. suum; the highest activity was found in the intestine.…”
Section: Discussionsupporting
confidence: 93%
“…The authors did not find any trypsin activity in any sample. In the present study, no lipase activity was found in any part of the A. suum organism, but esterase or esterase lipase were found in all samples, which is consistent with the results obtained by Lee (1962a), who found esterase activity in all the parts of the A. suum organism. Żółtowska and Łopieńska (1999) found the activity of lipase in all examined parts of A. suum; the highest activity was found in the intestine.…”
Section: Discussionsupporting
confidence: 93%
“…Intracellular records The cells ofAscaris described as muscle cells are extremely large ( > 100,u diameter), and it is a simple matter to introduce micro-electrodes (Jarman, 1959). There is some difficulty in interpreting the records in a manner consistent with published histological work on Ascaris (Chitwood & Chitwood, 1950;Lee, 1962 …”
Section: Spontaneous Activitymentioning
confidence: 99%
“…In the absence of any precise knowledge of the mechanism of neuromuscular transmission in Ascaris, however, it would be premature to conclude that piperazine produced neuromuscular block in a manner analogous to curare or decamethonium in vertebrates. The authors of publications presenting histological illustrations of ascarine muscle (Chitwood & Chitwood, 1950;Lee 1962) have suggested that the muscle cells are complex structures consisting of a large (> 100 ,u) globular 'non-contractile' portion with an 'innervation process' and a contractile part nearer the cuticle. Observation of these cells during contractions in response to electrical stimulation has confirmed the existence of longitudinally contracting muscle fibres, upon which the globular structures rest passively.…”
mentioning
confidence: 99%
“…Initially, a muscle strip preparation was used to measure muscle contraction in response to applied drugs, and, more recently, biochemical and electrophysiological techniques have been used to study identified neurons. Specifically, it has been shown that: (a) muscle cells depolarize and contract in response to exogenously applied ACh (Baldwin and Moyle, 1949;del Castillo, de Mello, and Morales, 1963;Aceves, Erlij, and Martinez-Maranon, 1970;Harrow and Gration, 1985); (b) d-tubocurarine (dTC) blocks these effects (Norton and de Beer, 1957;Martin, 1982) and also hyperpolarizes muscle cells (del Castillo et al, 1963); (c) acetylcholinesterase (ACHE), the enzyme that degrades ACh, is present at many sites, including the ends of the muscle projections (muscle arms) that receive synapses from neurons in the nerve cords (Lee, 1961); inhibitors of AChE produce tonic muscle contractions and potentiate the action of exogenous ACh (del Castillo et al, 1963;Knowles and Casida, 1966); (d) choline acetyhransferase, the synthetic enzyme for ACh, is present in excitatory motorneurons and in nerve cords, but not in inhibitory motorneurons (Johnson and Stretton, 1985). There is also evidence suggesting that ACh is a transmitter at certain neuron-neuron synapses, such as excitatory motorneuron to inhibitory motorneuron, and excitatory interneuron to excitatory motorneuron synapses (Kass, Stretton, and Wang, 1984).…”
Section: Introductionmentioning
confidence: 99%